3-Bromopyridine-Heterogenized Phosphotungstic Acid for Efficient Trimerization of Biomass-Derived 5-Hydroxymethylfurfural with 2-Methylfuran to C21 Fuel Precursor - Yufei Xu; Zhaozhuo Yu; Hu Li; Song Yang (Advances in Polymer Technology)
The production of long-chain carbon compounds (C9-C21) from biomass derivatives to alternate traditional fossil diesel is sustainable, eco-friendly, and potentially economic for modern industry. In this work, phosphotungstic acid heterogenized by 3-bromopyridine was achieved using a solvothermal method, which was demonstrated to be efficient for trimerization of biomass-derived 5-hydroxymethylfurfural (HMF) with 2-methylfuran (2-MF) to C21 fuel precursor (57.1% yield) under mild reaction conditions. The heterogeneous acidic catalyst could be reused for four consecutive cycles without obvious loss of activity, and different characterization techniques (e.g., XRD (X-ray diffraction), TG (thermogravimetric analysis), SEM (scanning electron microscope), FT-IR (Fourier transform infrared spectroscopy), and BET (Brunauer-Emmet-Teller)) were utilized to investigate the performance of the catalyst. In addition, a plausible reaction pathway was postulated, on the basis of results obtained by NMR (nuclear magnetic resonance) and GC-MS (gas chromatography-mass spectrometer). This strategy provides a facile and efficient approach to prepare a recyclable acidic catalyst for the production of diesel fuel precursor from biomass via controllable polymerization.